An Analysis of Stunting Determinants in North Tapanuli Regency - Emilia Silvana Sitompul; Juana Linda Simbolon; Marni Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
There has been a decline in stunting prevalence nationally in the last two years, requiring a more specific analysis of local determinants to optimize interventions at the regional level, especially in areas with geographical characteristics such as North Tapanuli Regency. This study aims to analyze the effect of nutritional intake, environmental sanitation, immunization status, and medical history on the incidence of stunting in toddlers. This quantitative study with a cross-sectional design involved 71 stunted toddler respondents in four working areas of the Community Health Center in North Tapanuli Regency. The data were analyzed using the Chi-Square test for bivariate analysis and Path Analysis to see the direct and indirect effects. The path analysis results showed that nutritional intake (0.365), sanitation (0.146), and immunization status (0.141) had a significant direct effect on stunting. Nutritional intake was the most dominant determining factor (p=0.010). Conversely, medical history (p=0.485) did not show a significant relationship and did not play a strong mediating role in this model. Nutritional intake is a key factor in determining the severity of stunting. Intervention strategies should focus on meeting the specific nutritional needs of toddlers in addition to improving sanitation and basic immunization coverageKeywords: Stunting, Nutritional Intake, Infectious Diseases, Sanitation, Immunization